THE EFFECT OF PRODUCT, BRAND ASSOCIATION, BRAND PERSONALITY AND ENDORSER IN INTENSE BUYING - Anang Firmansyah (Media Mahardhika, 2023)
This study is aimed to determine how the effect of endorser, brand association, brand personality and product characteristics in intense buying of Energy drinks Herbaviton. This study is took the 150 respondents and used judgmental sampling method. Data analysis techniques used factor analysis and multiple regression analysis. The results showed that the brand association and product characteristic significantly effect intense buying of Herbaviton, while the celebrity endorser and the brand personality does not significantly effect intense buying of Herbaviton. The Company should use the popular commercials person that have power and physical attraction or personality so can effect the consumer, and more attractive to the formation of a good brand personality and good product, because will be consumer in buying product which according to him.